Terrebonne Basin, Gulf of Mexico gas hydrate resource evaluation and 3-D modeling of basin-scale sedimentation, salt tectonics, and hydrate system evolution since the early Miocene - Laura N. Dafov; Zachary F.M. Burton; Seth S. Haines; Allegra Hosford Scheirer; Nicole Masurek; Ray Boswell; Matthew Frye; Yongkoo Seol; Stephan A. Graham (Marine and Petroleum Geology, 2025)

Bottom simulating reflections across the northern Gulf of Mexico slope - Aditya Kumar; Ann E. Cook; Alexey Portnov; Stuart Skopec; Matthew Frye; Stephen Palmes (Marine and Petroleum Geology, 2024)

Executive function mediates age-related variation in social integration in female vervet monkeys (Chlorocebus sabaeus) - Jacob D. Negrey; Brett M. Frye; Suzanne Craft; Thomas C. Register; Mark G. Baxter; Matthew J. Jorgensen; Carol A. Shively (GeroScience, 2023)

Correction to: Temporal emergence of age-associated changes in cognitive and physical function in vervets (Chlorocebus aethiops sabaeus) - Brett M. Frye; Payton M. Valure; Suzanne Craft; Mark G. Baxter; Christie Scott; Shanna Wise-Walden; David W. Bissinger; Hannah M. Register; Carson Copeland; Matthew J. Jorgensen; Jamie N. Justice; Stephen B. Kritchevsky; et al. (GeroScience, 2021)

Differential expression of miRNAs and functional role of mir-200a in high and low productivity CHO cells expressing an Fc fusion protein - Laura Bryan; Michael Henry; Niall Barron; Clair Gallagher; Ronan M. Kelly; Christopher C. Frye; Matthew D. Osborne; Martin Clynes; Paula Meleady (Biotechnology Letters, 2021)
Objectives We used miRNA and proteomic profiling to understand intracellular pathways that contribute to high and low specific productivity (Qp) phenotypes in CHO clonally derived cell lines (CDCLs) from the same cell line generation project. Results Differentially expressed (DE) miRNAs were identified which are predicted to target several proteins associated with protein folding. MiR-200a was found to have a number of predicted targets associated with the unfolded protein response (UPR) which were shown to have decreased expression in high Qp CDCLs and have no detected change at the mRNA level. MiR-200a overexpression in a CHO CDCL was found to increase recombinant protein titer by 1.2 fold and Qp by 1.8 fold. Conclusion These results may suggest a role for miR-200a in post-transcriptional regulation of the UPR, presenting miR-200a as a potential target for engineering industrially attractive CHO cell phenotypes.

Plant spectral diversity as a surrogate for species, functional and phylogenetic diversity across a hyper‐diverse biogeographic region - Henry A. Frye; Matthew E. Aiello‐Lammens; Douglas Euston‐Brown; Cynthia S. Jones; Hayley Kilroy Mollmann; Cory Merow; Jasper A. Slingsby; Helga van der Merwe; Adam M. Wilson; John A. Silander (Global Ecology and Biogeography, 2021)
Aim With plant biodiversity under global threat, there is an urgent need to monitor the spatial distribution of multiple axes of biodiversity. Remote sensing is a critical tool in this endeavour. One remote sensing approach for detecting biodiversity is based on the hypothesis that the spectral diversity of plant communities is a surrogate of multiple dimensions of biodiversity. We investigated the generality of this ‘surrogacy’ for spectral, species, functional and phylogenetic diversity across 1,267 plots in the Greater Cape Floristic Region (GCFR), a hyper‐diverse region comprising several biomes and two adjacent global biodiversity hotspots. Location The GCFR centred in south‐western and western South Africa. Time period All data were collected between 1978–2014. Major taxa studied Vascular plants within the GCFR. Methods Spectral diversity was calculated using leaf reflectance spectra (450–950 nm) and was related to other dimensions of biodiversity via linear models. The accuracy of different spectral diversity metrics was compared using 10‐fold cross‐validation. Results We found that a distance‐based spectral diversity metric was a robust predictor of species, functional and phylogenetic biodiversity. This result serves as a proof‐of‐concept that spectral diversity is a potential surrogate of biodiversity across a hyper‐diverse biogeographic region. While our results support the generality of spectral diversity as a biodiversity surrogate, we also find that relationships vary between different geographic subregions and biomes, suggesting that differences in broad‐scale community composition can affect these relationships. Main conclusions Spectral diversity was shown to be a robust surrogate of multiple dimensions of biodiversity across biomes and a widely varying biogeographic region. We also extend these surrogacy relationships to ecological redundancy to demonstrate the potential for additional insights into community structure based on spectral reflectance.

Temporal emergence of age-associated changes in cognitive and physical function in vervets (Chlorocebus aethiops sabaeus) - Brett M. Frye; Payton M. Valure; Suzanne Craft; Mark G. Baxter; Christie Scott; Shanna Wise-Walden; David W. Bissinger; Hannah M. Register; Carson Copeland; Matthew J. Jorgensen; Jamie N. Justice; Stephen B. Kritchevsky; et al. (GeroScience, 2021)